Textured macro- and mesoporous alumina samples designed in the presence of different surfactant types - Petrolini, Davi D. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Martins, Leandro [UNESP] (Springer, 2014)
This work presents a method that enables the synthesis of porous alumina in the presence of different types of surfactant. The method is based on a sol-gel transition, using surfactants and droplets of a nonpolar phase as templates. The main purpose was to establish a relationship between the templates and the resulting pore structure. The results show that depending on the type of surfactant used (ionic or nonionic), materials presenting variations in the pore family distribution, X-ray powder diffraction patterns and sample morphology were formed. During the synthesis of these alumina samples, the drying step caused loss of the porous structures, so the shrinkage due to different types of surfactants was evaluated.
Keywords: Porous alumina structures; Sol-gel; Surfactants; Dual soft templates; Gel retraction